A National Seroepidemiologic Survey of Pertussis Among School Children in Taiwan. Issue 12 (December 2017) - Lu, Chun-Yi; Tsai, Hsing-Chen; Huang, Yhu-Chering; Huang, Daniel Tsung-Ning; Liu, Ching-Chuan; Huang, Li-Min
Abstract : Background: In 2009, a booster dose of acellular pertussis vaccine for children at or before entry to elementary school was added to the national immunization program in Taiwan, which includes pertussis vaccination at 2, 4, 6 and 18 months of age. In 2013, a study to assess the level of humoral immunity against pertussis in elementary and junior high school children and adolescents was conducted. Methods: A multistage stratified systematic sampling method was applied to randomly selected grade 1 to 9 school children for testing. Serum samples were tested for IgG antibodies to Bordetella pertussis using commercial enzyme-linked immunosorbent assay kits. The study collected information on sociodemographic characteristics, vaccination history, sibling number and disease history of pertussis. Results: The study recruited 2782 school children from 58 schools around the country. By questionnaire, only 1% (28/2782) students had history of pertussis. The overall positivity rate of anti- B. pertussis IgG was 42.5%, and the rates were not different between the 5 geographical areas (range from 39.6% to 44.6%, P = 0.375). Age-stratified data showed that the positivity rates were 43.6–48.8% among grade 1–3 students, 26.6–28.7% in grade 4–5 students and increased progressively from 39.4% to 51.3% in grade 6–9 students. The overall positivity rate was significantly higher in the nonbooster group (46.4% versus 38.6%, P < 0.01). Conclusion: The prevalence of anti- B. pertussis antibody was 42.5% in grade 1–9 students under the current vaccination program in Taiwan. Antibody induced by the booster vaccination before entry of primary school waned rapidly in 3–4 years. Rapid waning of anti- B. pertussis antibody may explain the resurgence of whooping cough in recent decades. Additional booster doses should be considered in adolescents and adults.